The Comparisson between LBP and SQI Methods in the Surface Roughness Measurement Using ESPI Method - Mohammad Khoirul Effendi; Agus Sigit Pramono; Pandu Pratama; Rifki Wardana (IPTEK The Journal of Engineering, 2015)
Surface roughness measurement using direct contact methods raises several issues, for examples stylus wear and size limitation problems. Furthermore non-contact methods are proposed to solve these problems. One of them is Electronic Speckle Pattern Interferometry (ESPI), which use Helium-Neon (He - Ne) as laser light source. A speckle pattern is produced by scattered light on the surface of the measuring object due to the interference of laser beams, and it will be captured by Charge Coupled Device (CCD) camera. Afterwards Linear Binary Pattern (LBP) and Self Quotient Image (SQI) methods are used to reduce illumination effect in the captured image. The average gray-level from the previous process will be converted into a surface roughness value by gray level to surface roughness conversion formulation. It is obtained from correlation value between gray level and a set of standard roughness. The standard roughness value range is start from 0,05 μm to 12,5 μm. It is measured from five different final machining process, which are flat lapping, grinding, horizontal milling, and vertical milling. As verification, the results of ESPI method will be compared with the result of direct contact tools using Mitutoyo Surftest 301 and 401.